Pengaruh Model Pembelajaran Kooperatif Tipe Snowball Throwing Berbantuan Media Mind Mapping terhadap Hasil Belajar IPAS Materi Kekayaan Budaya Indonesia pada Peserta Didik Kelas IV di SDN Sumbersuko Kabupaten Probolinggo - Rosita Ayu Diastari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Abstract: This study was motivated by the low learning outcomes in IPAS on the topic of Indonesian Cultural Diversity among fourth-grade students at SDN Sumbersuko, Probolinggo Regency, which were caused by the limited variation of learning models and the dominance of conventional teaching methods. This study aimed to examine the effect of the Snowball Throwing cooperative learning model assisted by mind mapping media on students’ IPAS learning outcomes. This research employed a quasi-experimental design with a non-equivalent control group design. The research subjects consisted of 56 fourth-grade students, with class IVA as the experimental group and class IVB as the control group. Data were collected through tests in the form of pretests and posttests, while data analysis was conducted using the t-test and relative effectiveness analysis. The results showed that the calculated t-value was 4.692, which was greater than the t-table value of 2.004 at a 5% significance level, indicating that the hypothesis was accepted. The relative effectiveness test revealed that the implementation of the Snowball Throwing cooperative learning model assisted by mind mapping media had an effectiveness level of 33.17%. Therefore, it can be concluded that the Snowball Throwing cooperative learning model assisted by mind mapping media has a significant effect on IPAS learning outcomes on the topic of Indonesian Cultural Diversity among fourth-grade students at SDN Sumbersuko, Probolinggo Regency
FINALISASI oleh Agus 2026 Juni 04
Keywords: SNOWBALL THROWING; MIND MAPPING